Awareness and behavioral indicators of Maratabat among Maranao-Muslim children - Maranda, Alma G. (2009)
This study aims to identify some of the factors related to the acquisition and understanding of Maranao children's maratabat. Gaining insights into the Maranao children' maratabat may deepen understanding of their family values and eventually bring out satisfactory adjustment within their family. The study is significant inasmuch as it provides insights and rationale on why maratabat is considered a culture value by the Maranaos. This will enable other people, particularly non-Muslims, to understand Maranao behavior to foster mutual trust, respect, and cooperation among communities of differing beliefs and religion. In order to better understand the concept of maratabat among Maranao Muslim children, an exploratory survey-type study was conducted to investigate the factors that contribute to the understanding and practice of maratabat among Maranao Muslim children. The respondents consisted of 239 Maranao children in Marawi City. A self-administered questionnaire was the main instrument used to facilitate the gathering of data. Focused Group Discussion comprising the Maranao-Muslim children was used to further substantiate and clarify the information derived from the questionnaire. Maratabat is likewise behaviorally expressed or manifested through the following: showing strong family solidarity and cooperation, rido (family feud), sharing of expenses during ceremonies and defending family honor.
Keywords: Maratabat; Prestige; Maranao children; Mindanao studies